2020
DOI: 10.1111/puar.13177
|View full text |Cite
|
Sign up to set email alerts
|

Political Ideology and Social Services Contracting: Evidence from a Regression Discontinuity Design

Abstract: Theoretical perspectives on the ideological influences on government contracting predict that local governments controlled by right‐wing political parties will contract out a higher proportion of services than those controlled by left‐wing parties. However, empirical evidence on the impact of political ideology on contracting out remains inconclusive. To cast new light on this important issue, the authors apply a quasi‐experimental research design to contracting choices in children's social services in English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 88 publications
1
16
0
Order By: Relevance
“…Our findings echo those of others who have found a link between political control of councils and outsourcing (Dubin and Navarro 1988;Tavares and Camões 2010;Elinder and Jordahl 2013;Petersen, Houlberg, and Christensen 2015;Alonso and Andrews 2020). This research has found that centre-right councils are more likely to outsource services than centre-left authorities.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings echo those of others who have found a link between political control of councils and outsourcing (Dubin and Navarro 1988;Tavares and Camões 2010;Elinder and Jordahl 2013;Petersen, Houlberg, and Christensen 2015;Alonso and Andrews 2020). This research has found that centre-right councils are more likely to outsource services than centre-left authorities.…”
Section: Discussionsupporting
confidence: 89%
“…There is also evidence showing that political party control of councils is deterministic of sourcing decisions. Specifically, leftist councils appear to prefer in-house service provision and rightist councils outsourcing (Dubin and Navarro 1988;Tavares and Camões 2010;Elinder and Jordahl 2013;Petersen, Houlberg, and Christensen 2015;Alonso and Andrews 2020). These observations are consistent with partisan politics theory (Hibbs 1977(Hibbs , 1992, which predicts that the decisions taken by political parties reflect their supporters' interests and ideology.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this sense, the LA can take on a prominent role as the project planner and manager, also orchestrating the whole supply chain, and still achieving optimal efficiencies and optimal scale of operations (Garrone and Marzano, 2015). This could be particularly apparent in Local Authorities which are run by political parties which are less aligned to neo-liberal ideologies (Alonso and Andrews, 2020). Little evidence, however is presented on how, at a local level, planning-based ideologies translate into procurement practices and supply chain management and organisation of public projects, in an era in which PPP and PFI approaches represent the dominant model.…”
Section: Local Authorities and Supply Chain Planningmentioning
confidence: 99%
“…However, given the lack of internal capacity to manage this technology, election administration often favors networks of contractors to manage and troubleshoot election voting systems. Alonso and Andrews (2020) examine the role of political ideology in the contracting process. Research typically observes a partisan dimension to the make or buy decision, with local governments controlled by right‐wing political parties opting to contract out a higher proportion of services than those controlled by left‐wing parties.…”
mentioning
confidence: 99%